Automated conversion of Web-based marriage register data into a printed format with predefined layout - Brailsford, David F. (2011)
The Phillimore Marriage Registers for England were published in the period 1896 to 1922 and have defined a standard layout format for the typesetting of marriage data. However, not all English parish churches had their marriage registers analysed and printed by the Phillimore organisation within this time period. This paper tells the story of Wirksworth, a town in Derbyshire with a large church, licensed for marriages, yet whose marriage data was not released to the Phillimore organisation. Hence there is no printed Phillimore Marriages volume for Wirksworth. However, in recent years, a Wirksworth web site, created by John Palmer, has become famous as being probably the most comprehensive record of a parish’s activities anywhere on the Web. Within a total of 120 MB of data on the web site, covering events in Wirksworth from medieval times to the present, is a set of data recording births, marriages and deaths transcribed from the original hand-written church register volumes. The work described here covers the software tools and techniques that were used in creating a set of awk scripts to extract all the marriage records from the Wirksworth web site data. The extracted material was then automatically re-processed, typeset and indexed to form an entirely new Phillimore-style volume for Wirksworth marriages.